Penerapan Terapi Aktivitas Kelompok Sosialisasi untuk Meningkatkan Interaksi Sosial pada ODGJ di UPTD PSR-GPODGJ Palembang - Sawi Sujarwo; Rapina Pajaria (Yayasan Kawanad, 2026)
This study aimed to improve the social interaction skills of People with Mental Disorders (PMD) through the implementation of Group Socialization Activity Therapy (TAKS) at UPTD PSR-GPODGJ Palembang. The study employed a qualitative approach using an action study method involving six male participants aged approximately 30 years. The program was conducted in eleven sessions through various group activities, including self-introduction, sharing personal information, recognizing emotional expressions and gestures, question-and-answer games, introducing group members, sentence arrangement, sharing personal preferences, imitating movements and sounds, and expressing opinions about social responses. The results showed positive changes in the participants’ social interaction skills. Before participating in the program, most participants tended to be passive, were reluctant to speak, had limited eye contact, and showed limited interaction with other participants. After participating in the activities, the participants demonstrated greater confidence in introducing themselves and expressing their opinions, maintaining eye contact, communicating with group members, and showing helping and cooperative behaviors. Based on observations during the program, the implementation of TAKS showed positive changes in the participants’ social interaction skills and may serve as a supportive intervention in the social rehabilitation process for people with mental disorders.